CCL25 and CCR9 is a unique pathway that potentiates pannus formation by remodeling RA macrophages into mature osteoclasts. Issue 4 (25th January 2021) - Umar, Sadiq; Palasiewicz, Karol; Van Raemdonck, Katrien; Volin, Michael V.; Romay, Bianca; Ahmad, Imran; Tetali, Chandana; Sweiss, Nadera; Amin, M Asif; Zomorrodi, Ryan K; Shahrara, Shiva
Abstract: This study elucidates the mechanism of CCL25 and CCR9 in rheumatoid arthritis (RA). RA synovial fluid (SF) expresses elevated levels of CCL25 compared to OA SF and plasma from RA and normal. CCL25 was released into RA SF by fibroblasts (FLS) and macrophages (MΦs) stimulated with IL‐1β and IL‐6. CCR9 is also presented on IL‐1β and IL‐6 activated RA FLS and differentiated MΦs. Conversely, in RA PBMCs neither CCL25 nor CCR9 are impacted by 3‐month longitudinal TNF inhibitor therapy. CCL25 amplifies RA FLS and monocyte infiltration via p38 and ERK phosphorylation. CCL25‐stimulated RA FLS secrete potentiated levels of IL‐8 which is disrupted by p38 and ERK inhibitors. CCL25 polarizes RA monocytes into nontraditional M1 MΦs that produce IL‐8 and CCL2. Activation of p38 and ERK cascades are also responsible for the CCL25‐induced M1 MΦ development. Unexpectedly, CCL25 was unable to polarize RA PBMCs into effector Th1/Th17 cells. Consistently, lymphokine like RANKL was uninvolved in CCL25‐induced osteoclastogenesis; however, this manifestation was regulated by osteoclastic factors such as RANK, cathepsin K (CTSK), and TNF‐α. In short, we reveal that CCL25/CCR9 manipulates RA FLS and MΦ migration and inflammatory phenotype in addition to osteoclast formation via p38 and ERK activation. Abstract : Rheumatoid arthritis synovial fluid (RA SF) express markedly higher levels of CCL25 compared to osteoarthritis (OA) SF. We found that CCL25 is secreted from RA fibroblast like synoviocytes (FLS) and macrophages in response to IL‐1β and IL‐6 activation. Moreover, RA FLS and monocyte infiltration is potentiated by CCL25 through ERK and p38 phosphorylation. Extending these observations, inhibition of ERK and p38 pathways interferes with CCL25‐induced inflammatory phenotype in RA FLS and macrophages as well as its ability to promote osteoclastogenesis.